2006
DOI: 10.1111/j.1471-0528.2006.00960.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV and reproductive care—a review of current practice

Abstract: In developed countries, antiretroviral treatment has increased life quality and expectancy of HIV-infected individuals and led to a drop in mother-to-child transmission (MCT) risk to below 1%. Fertility has been shown to be reduced in both men and women with HIV. As a result of these factors, the demand for reproductive care in this population is rising. In discordant couples where the man is positive, sperm washing significantly reduces viral transmission risk to the uninfected female partner over unprotected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 72 publications
1
55
0
4
Order By: Relevance
“…One study (Bova and Durante 2003) found that the majority of women with HIV continued to be sexually active and that sexual activity was not related to HIV illness stage or functional status. Others studies have found psychosexual dysfunction among women with HIV (Gilling-Smith et al 2006;Bova and Durante 2003;Keegan et al 2005;Lambert et al 2005), although these symptoms were mostly among a small portion of the women interviewed and were unrelated to antiretroviral therapies (ART). For instance, Siegel, Schrimshaw and Lekas (2006) found that 30% of the women in their study experienced diminished pleasure on sex, diminished participation in sex, or diminished sense of sexual attractiveness.…”
Section: Introductionmentioning
confidence: 96%
“…One study (Bova and Durante 2003) found that the majority of women with HIV continued to be sexually active and that sexual activity was not related to HIV illness stage or functional status. Others studies have found psychosexual dysfunction among women with HIV (Gilling-Smith et al 2006;Bova and Durante 2003;Keegan et al 2005;Lambert et al 2005), although these symptoms were mostly among a small portion of the women interviewed and were unrelated to antiretroviral therapies (ART). For instance, Siegel, Schrimshaw and Lekas (2006) found that 30% of the women in their study experienced diminished pleasure on sex, diminished participation in sex, or diminished sense of sexual attractiveness.…”
Section: Introductionmentioning
confidence: 96%
“…These techniques, also known as ''sperm washing'' have been studied extensively and have shown to be highly successful in ensuring that mothers and children remain uninfected, as demonstrated by research spanning over two decades [6][7][8]. Further, providing an alternative to unprotected sexual intercourse for HIV serodiscordant couples who wish to conceive potentially reduces the spread of HIV [4]. Given that sexual transmission of HIV to women remains the leading cause of infection in the female population [2], assisted reproduction is particularly important for these couples.…”
Section: Introductionmentioning
confidence: 97%
“…Given that HIV positive men and women have consistently indicated that their own fertility desires were influenced by their partner's wishes [9,14,17,26], it is important to consider fertility desires in the context of a couple's relationship. HIV serodiscordant couples have a number of important issues to consider if they intend to have children, including the means by which to conceive, the potential risks involved in attempts to conceive, and the option of using donor sperm in the case of an HIV positive male partner [4]. Additionally, there are contingencies to consider in the event of the HIV positive partner's death [33], such as precautionary cryopreservation of gametes and third-party parenting arrangements.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…I read with great interest the review article by Gilling-Smith et al 1 on current practice in the reproductive care of HIVpositive individuals. As chairman of the centre with the single largest unit in Italy focused on the treatment of HIVserodiscordant (or concordant) couples, I was happy to agree with the views of Gilling-Smith et al…”
Section: Sirmentioning
confidence: 99%